2023
DOI: 10.1039/d2fo03129a
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum dietary intake, depression and the concentration of docosahexaenoic acid in mature breast milk in Wuhan, China

Abstract: Breast milk DHA proportion was positively associated with maternal aquatic product intake and DHA supplement use, and negatively associated with postpartum depression status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…DHA supplementation of 1.9 g/d for 8 weeks also did not exhibit a significant therapeutic effect on women who already developed PPD [ 130 ], and the result of Mendelian randomization did not demonstrate a causal relationship between n-3 PUFA intake and PPD [ 132 ]. In contrast, several recent studies have suggested an association between maternal DHA levels and PPD [ 133 ], as well as the preventive or therapeutic effects of DHA supplementation on PPD [ 134 , 135 ]. We compared the differences between different studies and found that the year of study was the most significant factor explaining the differences in conclusions.…”
Section: Postpartum Depression (Ppd)mentioning
confidence: 99%
See 1 more Smart Citation
“…DHA supplementation of 1.9 g/d for 8 weeks also did not exhibit a significant therapeutic effect on women who already developed PPD [ 130 ], and the result of Mendelian randomization did not demonstrate a causal relationship between n-3 PUFA intake and PPD [ 132 ]. In contrast, several recent studies have suggested an association between maternal DHA levels and PPD [ 133 ], as well as the preventive or therapeutic effects of DHA supplementation on PPD [ 134 , 135 ]. We compared the differences between different studies and found that the year of study was the most significant factor explaining the differences in conclusions.…”
Section: Postpartum Depression (Ppd)mentioning
confidence: 99%
“…Most of the negative studies [125][126][127][128][129][130][131][132] were conducted relatively early, with even the most recent negative studies [126,127] published in 2017. However, most of the positive studies [133][134][135] were conducted in recent years, all of which were performed after 2020. The specific effect of study years on this outcome is not clear.…”
Section: Postpartum Depression (Ppd)mentioning
confidence: 99%